Preparation method and application of highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material

CN119133484BActive Publication Date: 2025-02-25GUANGDONG OCEAN UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411282938.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-02-25
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The existing cobalt-modified nitrogen-sulphur co-doped layer pore carbon composite materials have complex preparation processes, difficult to regulate heteroatom distribution, and poor dispersion of cobalt components, which limits its application in secondary zinc air batteries.

Method used

By sulfate esterification modified chitosan as a precursor, the strong complex cooperative of sulfonic acid groups and divalent metal ions are self-assembled to generate uniformly distributed insoluble calcium sulfonate and cobalt sulfonate components, combined with roasting With acid leach treatment, the preparation of highly dispersed cobalt modified nitrogen and sulfur co-doped layered pore carbon composite material is realized.

Benefits of technology

The preparation process is simplified, and high-dispersed CoSx nanoparticles and precise N and S co-doping are achieved, which improves the electrocatalytic performance and stability of the material, and improves the cycle life and charge and discharge performance of the secondary zinc air battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133484B_ABST
    Figure CN119133484B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material, belonging to the technical field of electrocatalytic materials. The preparation method comprises the following steps: sulfation-modifying chitosan to obtain positioned sulfonated chitosan; adding the positioned sulfonated chitosan to a Ca-containing 2+ and Co 2+ The method comprises the following steps: stirring the mixture evenly in a solution of 200 μm and 30 μm, aging the mixture to obtain a positioning chitosan sulfonate mixture; calcining the positioning chitosan sulfonate mixture under an inert atmosphere, and acid leaching the calcined product to obtain the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material. The highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material provided by the present invention has a simple preparation process, good electrocatalytic activity and stability, and can be used as an electrocatalyst for secondary zinc-air batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic materials, and in particular relates to a preparation method and application of a highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material. Background Art

[0002] As the energy crisis intensifies, the development and utilization of electrochemical energy storage has become an inevitable choice for the current social development. Among many energy storage technologies, secondary zinc-air batteries have the advantages of low cost, high theoretical energy density, safety and environmental protection, and are regarded as one of the potential substitutes for the next generation of energy storage devices. They show great application potential in the fields of low-speed electric vehicles, wearable devices and smart grids.

[0003] However, the commercial application of secondary zinc-air batteries is currently slow. The key problem restricting its development is the slow ORR / OER kinetics occurring at the cathode, which leads to low energy conversion efficiency and cycle life. By constructing efficient and stable electrocatalysts and accelerating the ORR / OER reaction kinetics, the battery performance can be effectively improved. Commonly used precious metal-based catalysts, such as Pt / C, RuO2, etc., show good ORR or OER catalytic activity, but due to their scarce resources, high prices, poor stability, and single catalytic performance, they are difficult to be applied on a large scale for a long time. Therefore, the development of efficient and stable non-precious metal-based bifunctional electrocatalysts is the key to achieving high energy conversion efficiency and long cycle life of secondary zinc-air batteries, and is also an urgent need and key development direction for the development of the metal-air battery industry.

[0004] Among the many non-precious metal-based bifunctional electrocatalysts, transition metal sulfides represented by CoSx have the advantages of rich valence adjustable metal centers, good electrochemical stability and oxygen affinity, and have become one of the ideal alternative materials for precious metal catalysts. They have attracted the attention of many scholars in recent years. However, CoSx nanoparticles are prone to agglomeration during electrocatalysis, and their weak electronic conductivity also inhibits the long-term performance of the electrocatalytic performance of the material. Composite CoSx nanoparticles with carbon materials is an important means to effectively improve the conductivity and dispersibility of CoSx. However, there are still some problems in the practical application of composite materials. First, during long cycles, carbon materials with weak intrinsic electrocatalytic activity are prone to electrochemical corrosion under high OER potential and strong alkaline environment, resulting in the stripping of CoSx active components; secondly, it is still relatively difficult to maintain the high dispersion of CoSx nanoparticles on the carbon matrix during the preparation process.

[0005] At present, Chinese patent CN110665507A discloses a highly dispersed supported cobalt-based catalyst and its preparation method. First, a porous material is infiltrated with a cobalt salt solution to obtain a sample loaded with cobalt salt, and then mixed with 2-methylimidazole to prepare a metal cobalt organic framework material loaded on the porous material, and then a highly dispersed supported cobalt-based catalyst is obtained by carbonization treatment. The process is complicated and the cycle is long. At the same time, 2-methylimidazole and cobalt salt do not react completely at room temperature, which subsequently leads to a low heteroatom content of the product and poor dispersibility of the cobalt component. Chinese patent CN116259767A discloses the preparation and application of a sulfur-nitrogen doped single-atom cobalt-loaded porous carbon-sulfur composite positive electrode material. First, SiO-2@polydopamine-cobalt ion is synthesized, and then thiourea is used as a sulfur source to perform mixed carbonization and sulfur doping, and then a concentrated sodium hydroxide solution / hydrofluoric acid aqueous solution is used to remove the SiO2 template to obtain a sulfur-nitrogen doped single-atom cobalt-loaded porous carbon-sulfur composite material. The process is complicated, a large amount of chemical reagents are used in the preparation process, and the sulfurization process is mainly concentrated on the surface of the material, and the heteroatom content and distribution are difficult to control. Summary of the invention

[0006] In view of the problems of the existing cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite materials, such as the complicated preparation process, the difficulty in regulating the heteroatom distribution, and the poor dispersibility of the cobalt component, the present invention provides a preparation method and application of a highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material. The highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material prepared by the method can be used as an efficient secondary zinc-air battery electrocatalyst.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] One of the technical solutions of the present invention is to provide a method for preparing a highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material, comprising the following steps:

[0009] Chitosan is modified by sulfation to obtain positioned sulfonated chitosan; the positioned sulfonated chitosan is added to a Ca-containing 2+ and Co 2+ The solution is stirred evenly and aged to obtain a positioned chitosan sulfonate mixture; the positioned chitosan sulfonate mixture is roasted under an inert atmosphere, and the roasted product is acid-leached to obtain the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material.

[0010] Preferably, the specific steps of the sulfation modification include: mixing chitosan with an esterifying agent, reacting for 0.5 to 2 hours, precipitating with alcohol or ether, adding the precipitate to an alkaline solution, reducing the pH value of the alkaline solution to 6 to 9, filtering, and obtaining the positioned sulfonated chitosan;

[0011] The esterification agent is a 10-30wt.% trimethylamine·sulfur trioxide aqueous solution, a chlorosulfonic acid-DMF mixed solution with a volume ratio of 1:3-1:5, or a concentrated sulfuric acid-chlorosulfonic acid mixed solution with a volume ratio of 3:1-6:1.

[0012] More preferably, the solid-liquid ratio of the chitosan to the esterifying agent is 1 g:10-20 mL; the alkali solution is a solution prepared from one or two of Na2CO3, NaHCO3, K2CO3 and KHCO3, and its total concentration is 0.1-0.3 moL / L.

[0013] Preferably, the Ca-containing 2+ and Co 2+ Ca in solution 2+ The concentration of Co is 0.2~0.5mol / L, 2+ The concentration of the sulfonated chitosan is 0.05-0.1 mol / L; the positioning sulfonated chitosan and the Ca-containing 2+ and Co 2+ The solid-liquid ratio of the solution is 1g:10-20mL; the positioning sulfonated chitosan is added to the Ca-containing 2+ and Co 2+ The stirring time in the solution is 0.5 to 1 h, and the aging time is 0.5 to 1 h.

[0014] More preferably, the formulation contains Ca 2+ and Co 2+ The calcium salt used in the solution is one or more of calcium chloride, calcium nitrate, calcium acetate and calcium lactate, and the cobalt salt used is one or more of cobalt chloride, cobalt nitrate and cobalt acetate.

[0015] Preferably, the calcination temperature is 600-800° C., the calcination time is 1-3 hours, and the heating rate is 2-5° C. / min.

[0016] Preferably, the acid concentration in the acid solution used for the acid leaching is 0.1-0.5 mol / L, wherein the acid is one or two of hydrochloric acid, nitric acid and acetic acid.

[0017] The second technical solution of the present invention is to provide a highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material prepared according to the above preparation method.

[0018] The third technical solution of the present invention is to provide an application of the above-mentioned highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material in a secondary zinc-air battery electrocatalyst.

[0019] The beneficial technical effects of the present invention are as follows:

[0020] The present invention uses chitosan as a precursor and utilizes a sulfuric acid esterification reaction to introduce a sulfur source into specific groups of the chitosan molecule. By simply controlling the reaction time and the amount of the esterifying agent, a positioned sulfonated chitosan with a precise nitrogen and sulfur content can be obtained, thus avoiding the problem of the difficulty in regulating the precise distribution of traditional nitrogen and sulfur heteroatoms.

[0021] The present invention utilizes the strong complexation of sulfonic acid groups with divalent metal ions to self-assemble and generate uniformly distributed insoluble calcium sulfonate and cobalt sulfonate components, which act as templates. The roasting process releases sulfur dioxide gas, which can realize the construction of in-situ hierarchical pore structure and in-situ sulfur doping. In addition, the pyrolysis ash CaO can be further treated with simple dilute acid to enrich the pore structure distribution, which can effectively improve the electrocatalytic mass transfer process of the carbon material.

[0022] The chitosan selected in the present invention is rich in nitrogen and can be directly and evenly doped with nitrogen in situ during the calcination process. It has a synergistic effect with sulfur atoms and can effectively improve the electrocatalytic performance of carbon materials.

[0023] The pore structure constructed in situ during the pyrolysis of self-assembled sulfonates can be CoS x The in-situ nucleation and growth of Co can be confined, and the sulfide bonds generated by the abundant sulfur doping around the pore structure can serve as sulfur sources, inducing the 2+ Anchoring nucleation is carried out at the sulfur-doped sites, and the combination of the two will help to construct highly dispersed CoSx nanoparticles and improve the stability of the composite material.

[0024] The present invention regulates the content and particle size of self-assembled calcium sulfonate by regulating the aging time and calcium salt concentration of calcium sulfonate, thereby achieving precise regulation of pore structure distribution during pyrolysis, thereby avoiding the problem that it is difficult to precisely regulate the traditional pore structure.

[0025] The self-assembly template-assisted pyrolysis method proposed in the present invention can controllably prepare highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite materials, simplifying the preparation process of cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite materials, while avoiding the problems of uneven distribution of traditional external template agents leading to insufficient pore structure and difficult to control the dispersion of cobalt components. The process has strong repeatability and is easy to carry out large-scale production.

[0026] The highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material prepared by the present invention has the microstructural characteristics of highly dispersed CoSx nanoparticles, precise N, S co-doping and hierarchical porous structure. As a secondary zinc-air battery electrocatalyst, its highly dispersed CoSx nanoparticles can construct abundant catalytic active sites and improve the electrochemical stability of carbon materials; abundant nitrogen and sulfur heteroatoms can regulate the electron transfer efficiency of the composite material; the hierarchical porous structure can effectively increase the wettable area of ​​the electrolyte, expose more catalytic active sites, and provide abundant diffusion paths for electrolyte and oxygen molecules, reduce the diffusion resistance of electrolyte and oxygen molecules, promote the adsorption and desorption behavior of oxygen molecules and intermediate products on the surface of the material during the electrocatalytic process, and finally improve the cycle life and charge and discharge performance of the device.

[0027] The highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material provided by the present invention has a simple preparation process, good electrocatalytic activity and stability, and can provide a certain theoretical reference for the development and design of other non-precious metal bifunctional electrocatalysts for secondary zinc-air batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a TEM image of the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material prepared in Example 3 of the present invention.

[0029] Figure 2 This is the XRD pattern of the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material prepared in Example 3 of the present invention.

[0030] Figure 3 This is a comparison chart of the catalytic activities of the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material prepared in Example 3 of the present invention and commercial Pt / C.

[0031] Figure 4 This is a comparison chart of the catalytic activities of the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material prepared in Example 3 of the present invention and commercial RuO2.

[0032] Figure 5 This is a graph showing the cycling performance of the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material prepared in Example 3 of the present invention and commercial Pt / C+RuO2 for secondary zinc-air batteries. DETAILED DESCRIPTION

[0033] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0034] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0035] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0037] Example 1

[0038] Preparation of highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composites:

[0039] a. 5 g of chitosan was added to 50 mL of an aqueous solution containing 15 wt.% trimethylamine·sulfur trioxide, and the reaction was stirred for 1 h before adding anhydrous ethanol for alcohol precipitation. The precipitate was added to a 0.3 mol / L K2CO3 solution to reduce the pH value of the K2CO3 solution to 9, filtered, and the precipitate was freeze-dried to obtain a yellow positioning sulfonated chitosan;

[0040] b. The positioning sulfonated chitosan in step a was added to a mixed solution containing 0.2 mol / L calcium lactate and 0.05 mol / L cobalt nitrate, the solid-liquid ratio was controlled to 1g: 10mL, stirred for 0.5h, matured for 1.0h, and filtered to obtain a light pink positioning chitosan sulfonate mixture;

[0041] C. drying the positioned chitosan sulfonate mixture obtained in step b and transferring it into a tube furnace, calcining it under an argon atmosphere, and naturally cooling it to room temperature, wherein the calcination temperature is 600° C., the holding time is 2.0 h, and the heating rate is 2° C. / min;

[0042] d. The calcined product obtained in step c was soaked in 0.1 mol / L nitric acid solution, subjected to ultrasound for 0.5 h, and then repeatedly washed with deionized water and ethanol, and dried in a forced air drying oven at 60 °C overnight to obtain a highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material, denoted as CoSx@NSPC.

[0043] Example 2

[0044] Preparation of highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composites:

[0045] a. Add 5 g of chitosan powder to 75 mL of chlorosulfonic acid-DMF mixture (volume ratio 1:3), stir and react in a 50°C water bath for 1.5 h, then add anhydrous ethanol for alcohol precipitation, add the precipitate to K2CO3 (0.15 mol / L) + NaHCO3 (0.1 mol / L) solution, and reduce the pH value of the K2CO3 + NaHCO3 mixed solution to 7, filter, and freeze-dry the precipitate to obtain yellow localized sulfonated chitosan;

[0046] b. The positioning sulfonated chitosan in step a was added to a mixed solution containing 0.3 mol / L calcium acetate and 0.1 mol / L cobalt chloride, the solid-liquid ratio was controlled to 1g: 15mL, stirred for 1.0h, aged for 1.0h, and filtered to obtain a light pink positioning chitosan sulfonate mixture;

[0047] c. The chitosan sulfonate mixture in step b was dried and transferred into a tube furnace, calcined under a nitrogen atmosphere, and naturally cooled to room temperature, wherein the calcination temperature was 650°C, the holding time was 2.5h, and the heating rate was 5°C / min;

[0048] d. The calcined product obtained in step c was soaked in 0.2 mol / L acetic acid solution, subjected to ultrasound for 0.5 h, and then repeatedly washed with deionized water and ethanol, and dried in a forced air drying oven at 60 °C overnight to obtain a highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material, denoted as CoSx@NSPC.

[0049] Example 3

[0050] Preparation of highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composites:

[0051] a. Add 5 g of chitosan powder to 100 mL of pre-cooled (-20 ° C) concentrated sulfuric acid-chlorosulfonic acid mixture (volume ratio of 3:1), stir and react for 2 h, then add ice ether for ether precipitation, add the precipitate to K2CO3 (0.25 mol / L) solution, reduce the pH value of the K2CO3 solution to 8, filter, and freeze-dry the precipitate to obtain yellow localized sulfonated chitosan;

[0052] b. The positioning sulfonated chitosan in step a was added to a mixed solution containing 0.5 mol / L calcium chloride and 0.08 mol / L cobalt chloride, the solid-liquid ratio was controlled to 1g: 20mL, stirred for 0.5h, aged for 1.0h, and filtered to obtain a light pink positioning chitosan sulfonate mixture;

[0053] c. The chitosan sulfonate mixture in step b was dried and transferred into a tube furnace, calcined under an argon atmosphere, and naturally cooled to room temperature, wherein the calcination temperature was 700°C, the holding time was 2.5h, and the heating rate was 3°C / min;

[0054] d. The calcined product obtained in step c was soaked in 0.2 mol / L hydrochloric acid solution, subjected to ultrasound for 0.5 h, and then repeatedly washed with deionized water and ethanol, and dried in a forced air drying oven at 60 °C overnight to obtain a highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material, denoted as CoSx@NSPC.

[0055] Example 4

[0056] Preparation of highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composites:

[0057] a. Add 5 g of chitosan powder to 75 mL of pre-cooled (-20 ° C) concentrated sulfuric acid-chlorosulfonic acid mixture (volume ratio of 4:1), stir and react for 1 h, then add ice ether for ether precipitation, add the precipitate to KHCO3 (0.05 mol / L) + Na2CO3 (0.2 mol / L) solution, and reduce the pH value of the KHCO3 + Na2CO3 mixed solution to 6, filter, and freeze-dry the precipitate to obtain yellow localized sulfonated chitosan;

[0058] b. The positioning sulfonated chitosan in step a was added to a mixed solution containing 0.3 mol / L of calcium lactate and 0.05 mol / L of cobalt nitrate, the solid-liquid ratio was controlled to 1g: 15mL, stirred for 1.0h, aged for 0.5h, and filtered to obtain a light pink positioning chitosan sulfonate mixture;

[0059] c. The chitosan sulfonate mixture in step b was dried and transferred into a tube furnace, calcined under a nitrogen atmosphere, and naturally cooled to room temperature, wherein the calcination temperature was 750°C, the holding time was 3.0h, and the heating rate was 3°C / min;

[0060] d. The calcined product obtained in step c was soaked in 0.5 mol / L hydrochloric acid solution, ultrasonicated for 0.5 h, then repeatedly washed with deionized water and ethanol, and dried in a forced air drying oven at 60°C overnight to obtain a highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material, denoted as CoSx@NSPC.

[0061] Example 5

[0062] Preparation of highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composites:

[0063] a. Add 5 g of chitosan powder to 60 mL of chlorosulfonic acid-DMF mixture (volume ratio 1:5), stir and react in a 45°C water bath for 1 h, then add anhydrous ethanol for alcohol precipitation, add the precipitate to a solution of K2CO3 (0.1 mol / L) + KHCO3 (0.1 mol / L), and reduce the pH value of the K2CO3 + KHCO3 solution to 9, filter, and freeze-dry the precipitate to obtain yellow localized sulfonated chitosan;

[0064] b. The positioning sulfonated chitosan in step a was added to a mixed solution containing 0.3 mol / L calcium acetate and 0.08 mol / L cobalt acetate, the solid-liquid ratio was controlled to 1g: 20mL, stirred for 1.0h, aged for 0.5h, and filtered to obtain a light pink positioning chitosan sulfonate mixture;

[0065] c. The chitosan sulfonate mixture positioned in step b was dried and transferred to a tube furnace, calcined under a nitrogen atmosphere, and naturally cooled to room temperature, wherein the calcination temperature was 800°C, the holding time was 1.0h, and the heating rate was 5°C / min;

[0066] d. The calcined product obtained in step c was soaked in 0.4 mol / L nitric acid solution, subjected to ultrasound for 0.5 h, and then repeatedly washed with deionized water and ethanol, and dried in a forced air drying oven at 60 °C overnight to obtain a highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material, denoted as CoSx@NSPC.

[0067] The TEM image of CoSx@NSPC prepared in Example 3 is shown in Figure 1 .Depend on Figure 1 It can be seen that CoSx@NSPC has rich hierarchical pore structure and highly dispersed CoSx nanoparticles.

[0068] The XRD pattern of CoSx@NSPC prepared in Example 3 is shown in Figure 2 .

[0069] Comparison of the catalytic activity of CoSx@NSPC prepared in Example 3 with commercial Pt / C and RuO2, the test method is: LSV determination, 5mV / s. The catalytic activity comparison of CoSx@NSPC and commercial Pt / C is shown in Figure 3 The catalytic activity comparison of CoSx@NSPC and commercial RuO2 is shown in Figure 4 .

[0070] Comparison of the cycling stability of CoSx@NSPC prepared in Example 3 and commercial Pt / C+RuO2 for secondary zinc-air batteries, the method is: the charge and discharge current density is 10mA / cm 2 The charge and discharge cycle is 20 minutes. Figure 5 .

[0071] Depend on Figure 3 to Figure 5 It can be seen that the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material prepared by the present invention has similar electrocatalytic activity to other high-performance material catalysts available on the market. At the same time, applying it to secondary zinc-air batteries can effectively improve the electrochemical performance of secondary zinc-air batteries.

[0072] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material, characterized in that: The following steps are involved: Chitosan is modified by sulfation to obtain positioned sulfonated chitosan; the positioned sulfonated chitosan is added to a Ca-containing 2+ and Co 2+ The solution is stirred evenly and aged to obtain a positioning chitosan sulfonate mixture; the positioning chitosan sulfonate mixture is roasted under an inert atmosphere, and the roasted product is acid-leached to obtain the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material CoS x @NSPC; The esterifying agent in the sulfuric acid esterification modification is a 10-30wt.% trimethylamine·sulfur trioxide aqueous solution, a chlorosulfonic acid-DMF mixture with a volume ratio of 1:3-1:5, or a concentrated sulfuric acid-chlorosulfonic acid mixture with a volume ratio of 3:1-6:

1.

2. The method for preparing the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material according to claim 1, characterized in that: The specific steps of the sulfation modification include: mixing chitosan with an esterifying agent, reacting for 0.5 to 2 hours, precipitating with alcohol or ether, adding the precipitate into an alkaline solution, reducing the pH value of the alkaline solution to 6 to 9, filtering, and obtaining the positioned sulfonated chitosan.

3. The method for preparing the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material according to claim 2, characterized in that: The solid-liquid ratio of the chitosan to the esterifying agent is 1g:10-20mL; the alkali solution is a solution prepared from one or two of Na2CO3, NaHCO3, K2CO3 and KHCO3, and its total concentration is 0.1-0.3 mol / L.

4. The method for preparing the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material according to claim 1, characterized in that: The Ca-containing 2+ and Co 2+ Ca in solution 2+ The concentration of Co is 0.2~0.5 mol / L. 2+ The concentration of the sulfonated chitosan is 0.05-0.1 mol / L; the positioning sulfonated chitosan and the Ca-containing 2+ and Co 2+ The solid-liquid ratio of the solution is 1g:10~20mL; the positioning sulfonated chitosan is added to the Ca-containing 2+ and Co 2+ The stirring time in the solution is 0.5~1h, and the aging time is 0.5~1h.

5. The method for preparing the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material according to claim 1, characterized in that: The calcination temperature is 600-800° C., the calcination time is 1-3 hours, and the heating rate is 2-5° C. / min.

6. The method for preparing the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material according to claim 1, characterized in that: The acid concentration in the acid solution used for the acid leaching is 0.1-0.5 mol / L, wherein the acid is one or two of hydrochloric acid, nitric acid and acetic acid.

7. A highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material prepared according to the preparation method according to any one of claims 1 to 6.

8. Use of the highly dispersed cobalt-modified nitrogen-sulfur co-doped hierarchical porous carbon composite material as claimed in claim 7 in secondary zinc-air battery electrocatalyst.

Citation Information

Patent Citations

  • Highly dispersed supported cobalt-based catalyst and preparation method thereof

    CN110665507A

  • Preparation and application of sulfur-nitrogen-doped monatomic cobalt-loaded porous carbon-sulfur composite positive electrode material

    CN116259767A

  • Co-based MOFs-heteroatom doped porous carbon catalyst for oxygen reduction and preparation method thereof

    CN111185218A

  • Preparation method and application of S-Co-N in-situ co-doped porous carbon

    CN112599800A